2021
DOI: 10.1186/s13071-021-04857-5
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity, canalisation and developmental stability of Triatoma infestans wings: effects of a sublethal application of a pyrethroid insecticide

Abstract: Background Triatomine control campaigns have traditionally consisted of spraying the inside of houses with pyrethroid insecticides. However, exposure to sublethal insecticide doses after the initial application is a common occurrence and may have phenotypic consequences for survivors. Here, using Triatoma infestans (the main vector of Chagas disease in the Southern Cone of South America) as a model species, we quantified the effects of exposure to a sublethal dose of pyrethroid insecticide on w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…It is also possible that anthropogenic environmental stressors in the communities, such as the excessive application and prolong use of insecticides by households to control bed bugs in the study area as evidenced in our previous investigations ( Deku et al 2021 ), may introduce environmental pressures resulting in morphological shape differentiation. Recently, it has been reported that, phenotypic integrity of populations of Triatoma infestans were affected by sublethal doses of pyrethroid insecticides ( Nattero et al 2021 ). However, it is not presently known if this has contributed to the observed body shape variability in C. hemipterus and if there are implications for control, or why insecticide selection pressure would lead to changes in body shape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that anthropogenic environmental stressors in the communities, such as the excessive application and prolong use of insecticides by households to control bed bugs in the study area as evidenced in our previous investigations ( Deku et al 2021 ), may introduce environmental pressures resulting in morphological shape differentiation. Recently, it has been reported that, phenotypic integrity of populations of Triatoma infestans were affected by sublethal doses of pyrethroid insecticides ( Nattero et al 2021 ). However, it is not presently known if this has contributed to the observed body shape variability in C. hemipterus and if there are implications for control, or why insecticide selection pressure would lead to changes in body shape.…”
Section: Discussionmentioning
confidence: 99%
“…This pressure can alter the genetic and morphological life history of a species. This has been evident in some Hemipteran pest populations, such as Triatoma infestans (Hemiptera: Reduviidae), where the insect phenotypic integrity was reported to be affected by sublethal doses of pyrethroid insecticides ( Nattero et al 2021 ).…”
mentioning
confidence: 99%
“…For this reason and considering the low number of adult individuals that could be included in the experiment with no acetone application, we only included the control group inoculated with acetone. The topical applications with technical-grade deltamethrin (99% purity; Sigma-Aldrich, Buenos Aires, Argentina) were done as described in Nattero et al (2021). Analytical-grade acetone was purchased from Merck (Buenos Aires, Argentina).…”
Section: Experimental Designmentioning
confidence: 99%
“…Of the 25 and 19 full-sib families existing at the onset, we ended up with 14 (susceptible) and 10 (resistant) full-sib families, each of which included 5 to 15 adult insects, due to the low number of adults obtained in control and deltamethrin-treated groups in some (2021) were included in this study to avoid a large disparity with respect to the susceptible population. For the susceptible population, about half of them (48%) survived the application of deltamethrin (Nattero et al, 2021). In the resistant population, 96% of the nymphs survived the application of deltamethrin and moulted to the adult stage.…”
Section: Sample Sizesmentioning
confidence: 99%
See 1 more Smart Citation